Kudus Exhibition Center Penekanan Pada Arsitektur Post Modern - utomo, feri prasetyo; , Dr. Ir. Dhani Mutiari, MT; , MS Priyono Nugroho, ST, MT (2016)
Exhibition Center Holy emphasis on Post Modern Architecture is a building of the central container of coordination of activities related to the conference and exhibition providing the facilities and the ingredients in the sanctuary with an emphasis on post-modern architecture by combining the characteristic of the holy city with Modern Architecture. The background of the establishment of the Holy Exhibition Center this because of limited space or container for MICE activities in Kudus very limited and does not have the complete facilities and the presence of the Holy Exhibition Center is expected to push the rate of the economy in the Holy city. Implementation of the Convention and the exhibition is expected to be a trigger for the development of industrial economy. From the context of the above relationship can be seen that the activities of the convention and exhibition business activities. Coupled with the Holy enormous potential in the convention and exhibition sector. The absence of a building Exhibition Center Holy specifically accommodate the activities of convention and exhibition facilities and ingredients that give in the Holy city. Of the potential of the Holy city, the Holy Exhibition Center is the perfect set up in the Holy city and the future prospects expected to overcome the existing obstacles to the development and advancement of the Holy city.